Study on electron emission by a spherical object: dynamics of trapped particles. (April 2019) - Coppa, G.; Mulas, R.
Abstract : In this paper, the dynamics of electrons emitted by a spherical object when the total charge of the system is constant is studied in detail. In particular, the condition for which the total electron charge presents damped oscillations is deduced rigorously by considering a perturbation with respect to the steady-state solution. The results obtained can be of utility in simulating the expansion of a spherical plasma by separating the ion and electron time scales.